If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0 = 6a(3 + 4) + -3(a + 2) Combine like terms: 3 + 4 = 7 0 = 6a(7) + -3(a + 2) Reorder the terms for easier multiplication: 0 = 6 * 7a + -3(a + 2) Multiply 6 * 7 0 = 42a + -3(a + 2) Reorder the terms: 0 = 42a + -3(2 + a) 0 = 42a + (2 * -3 + a * -3) 0 = 42a + (-6 + -3a) Reorder the terms: 0 = -6 + 42a + -3a Combine like terms: 42a + -3a = 39a 0 = -6 + 39a Solving 0 = -6 + 39a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-39a' to each side of the equation. 0 + -39a = -6 + 39a + -39a Remove the zero: -39a = -6 + 39a + -39a Combine like terms: 39a + -39a = 0 -39a = -6 + 0 -39a = -6 Divide each side by '-39'. a = 0.1538461538 Simplifying a = 0.1538461538
| 6a(3+4)-3(a+2)= | | 5x-8=3-2x | | 9x-11=8x+4 | | (9x+4)=5 | | 8x-11=x+20+6x-12 | | -0.82x=-1.2 | | 2x+4=5x-4 | | x+1+2=3x | | 3x/12-2x-4/12=4x/12 | | 49.52=28.485lnx+11.13 | | 19=6x+13 | | 19.52=28.485lnx+11.13 | | 11x-20=5x+16 | | -110x^2-72x-10=0 | | 16x+3=13x+9 | | 8x-16=x+26 | | Y-3/13=-2/13 | | 3(2)+2(3x)=24 | | 0.4+0.7=0.9 | | 36m^2-25/36=0 | | -90x^2+1x+72=0 | | -2/7x-5/12= | | 5y-7x=35z | | 7x-4=6x+10 | | 8y-7=6-2y-10y | | -3x+2.8=-11.2 | | 10/17=h/119 | | -0.825+0.57-(-0.62)+0.155= | | 3•x/5-0.5=1.9 | | (3-z)(4z+2)=0 | | 46.65=29.28lnx+5.27 | | 18/27=x/18 |